Climate change mitigation: comparative assessment of Malaysian and ASEAN scenarios - Rasiah R.; Ahmed A.; Al-Amin A.Q.; Chenayah S. (Springer Verlag, 2023)
ASEAN; carbon emission; climate change; comparative study; downscaling; economic analysis; empirical analysis; environmental economics; environmental policy; mitigation; Malaysia; carbon; carbon dioxide; carbon cycle; climate; climate change; ecology; Malaysia; temperature; theoretical model; Carbon; Carbon Cycle; Carbon Dioxide; Climate; Climate Change; Ecology; Malaysia; Models, Theoretical; Temperature